Successful epilepsy surgery in a patient with neurosarcoidosis - Malmgren, Kristina; Lycke, Jan; Engman, Elisabeth; Hedström, Anders; Jönsson, Lars; Rydenhag, Bertil; Nordborg, Claes (Epilepsia (Copenhagen), 2010)
Summary This case concerns a patient with generalized neurosarcoidosis and pharmacoresistant focal epilepsy. Although immunosuppressive therapy resulted in remission of the neurosarcoidosis, seizures continued and were shown to originate from the right temporal lobe (TL). The patient underwent a right anterior temporal lobe resection (TLR) and obtained >90% reduction of seizure frequency.